Procesni položaj upravitelja pri razpolaganju z (nevknjiženo) nepremičnino - Vodopivec, Katarina (Podjetje in delo, 2013)
The author deals with legal person (debtor in bankruptcy) as owner of rights in rem, powers of the bankruptcy trustee in bankruptcy proceedings and Land registry proceedings. It is about the Land registration of erased legal entity for the disposal of subsequently found real estate in bankruptcy proceedings. Discussion leads to the legal regulations about status and obligations of bankruptcy trustee to arrange Land registration for (erased) debtor in bankruptcy from the theoretical and practical point of view.
Keywords: insolventnost; nepremičnine; pravne osebe; stečaj; stečajni dolžniki; stečajni postopek; zemljišča; zemljiške knjige